Technology and Innovation Report 2010 - United Nations Conference on Trade; Development (United Nations, 2010)
The 2010 Technology and Innovation Report - Enhancing Food Security in Africa Through Science, Technology and Innovation - focuses on the challenges of improving agricultural performance in Africa and the role of technology and innovation in raising agricultural production and incomes of all farmers, including smallholder farms. The report argues that the main challenge is to strengthen the innovation capabilities of African agricultural systems as a means of addressing poverty, improving food security and achieving broader economic growth and development.